Asas Praduga Tak Bersalah dalam Kasus Anak yang Dilibatkan Orang Dewasa dalam Pencurian di Bawah Paksaan - Muhammad Yusuf; Hendrik Dengah; Mursani Mursani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This study examines the application of the principle of presumption of innocence to children involved in theft due to coercion by adults. Children as vulnerable subjects of law are often exploited or pressured to commit criminal acts against their free will, raising critical questions about the proper legal protection. Using normative juridical methods through legislative approaches and case studies, this study analyzes Indonesian regulations, especially Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, as well as relevant judicial practices. The results of the study show that although the principle of presumption of innocence is a fundamental legal guarantee, its application in the case of children is still inconsistent. Law enforcement officials tend to prioritize a repressive approach, ignoring the psychological condition of children and coercive elements that eliminate the element of error (mens rea). Theoretically, this study uses legal protection theory, justice theory, and restorative justice principles, with an emphasis that children who are forced to commit crimes should be seen as victims of exploitation. The conclusion of the study confirms that the effectiveness of legal protection depends on the consistency of the application of the principle of presumption of innocence, the integration of restorative approaches, and strong institutional support to ensure the best interests of children.